Evaluation of quality of life and the nutritional status of oral cancer treated patients as compared with the control group in Varanasi district: a cross sectional study - Singh, Vishal; Singh, Ashok Kumar; Dutta, Kumar Durga; Kumar, Neeraj; Kumari, Anu (International Journal Of Community Medicine And Public Health, 2019)
Background: The modern day oral oncotherapy is now concerned on the oral quality of life after treatment of the patient. There is need to evaluate final outcome following the different combination of treatment modalities available to make better therapeutic treatment decisions. Oral health-related quality of life (QHRQOL) and their nutritional status is gaining importance as a valuable outcome measure in oral cancer area and compare with the other control group. The aim of the study was to examine the nutritional status among the oral cancer patients and compare the QHRQoL of two groups (i.e., oral cancer group and control group) in Varanasi district. Methods: The prospective study was conducted from January 2018 to August 2018. 124 oral cancer patients and 124 control people from the Varanasi district participated in this study. Nutritional status of oral cancer treated patients was assessed. QHRQoL of the oral cancer patients were compared with the control group. Results: Among the 124 oral cancer patient, 67.74% were malnourished or at risk of malnutrition. Patients had worse QHRQoL among oral cancer group. There were highly statistically significant differences found in the oral health impact profile and oral impacts on daily performances on comparing the oral cancer patients with the control group. Conclusions: This study indicated that oral cancer patients with malnutrition or risk of malnutrition have significantly worse OHRQoL than with the control population group.